Student Perceptions of Interprofessional Education Innovation to Address Pain Management and Substance Use: A Qualitative Descriptive Analysis. - Kobayashi, Rie; Miller, Jennifer C.; Remsberg, Connie M.; McKennon, Skye; Bindler, Ross J.; DeWitt, Dawn E.; Wilson, Marian (Journal of Advanced Nursing (John Wiley & Sons, Inc.), 2026)
Aims: The aim of this study was to understand student perspectives regarding an interprofessional education (IPE) innovation using a single standardised patient (SP) in a large‐group setting for a pain management and substance use simulation. Design: A qualitative descriptive design was used. Method: Students representing eight health science programs from four universities were invited to participate in a simulation‐based IPE program blending asynchronous and synchronous learning. DNP students were one of the largest professions represented (n = 92, 30%) along with students enrolled in Doctor of Pharmacy (n = 111) and Doctor of Medicine (n = 69) programs. Students were invited to complete a post‐activity survey asking what parts of the IPE activity were most valued and what could be improved. Student responses were themed using a qualitative descriptive approach with inductive coding and constant comparison. Results: Of 304 participating students, 155 (51%) responded to one or both open‐ended questions. Respondents highly valued interprofessional team diversity. Responses highlighted the importance of: (1) using simulation with student teams to foster active learning, (2) student preparation using relevant curricular resources and (3) grounding interprofessional collaboration activities in student engagement and professional respect. Conclusion: Findings confirmed that a cost‐effective IPE activity using one SP within deliberately planned interprofessional activities can be engaging and meaningful. Students valued team‐based collaboration across the disciplines of nursing, pharmacy and medicine. Impact: Educators gathered evidence on the merits of a replicable, cost‐effective IPE structure intended to expand team‐based simulation learning opportunities. High‐priority public health topics such as pain and substance use require multidisciplinary, integrative care to maximise health outcomes. To better prepare nurses and their health science collaborators, novel pedagogy in IPE may optimise student learning experiences. Reporting Method: We followed the Standards for Reporting Qualitative Research (SRQR). Patient or Public Contribution: Health sciences faculty served as facilitators in the IPE sessions. Facilitators were provided 1 h of training and observed student team breakout rooms to ensure that students were engaged and understood the assigned task. They provided feedback to session leaders after the sessions.